Does Cash Holding, Intellectual Capital, Gender Diversity of the Board of Directors Affect Firm Value? - Anggraini, Aulia Kus; Lestari, Tri Utami (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The purpose of this research was to determine the relationship between firm valuend cash holdings, intellectual capital, and gender diversity on the board of directors. Companies in the non-cyclical consumer sector that are listed on the Indonesia Stock Exchange (IDX) for the years 2017 through 2021 make up the study's population. Purposive sampling was utilised in the sample selection for this research, resulting in the collection of 18 firms with five years and 90 data observations. The findings of hypothesis testing reveal that firm value is influenced by cash holdings, intellectual capital, and the gender diversity of the board of directors. A favourable impact on firm value is partially provided by intellectual capital and the gender diversity of the board of directors. Cash Holding has little impact on a firm value, though. Future researchers is suggested to reexamine the cash holding variable based on the research findings since the variable in this study had no impact on firm value.